Female Runner With Painful Left Thigh Swelling: A Case of May‐Thurner Syndrome. Issue 2 (27th June 2017) - Petrin, Ziva; Wowkanech, Charles; Sinha, Anupam N.; Gupta, Sunny; Patel, Mitesh K.
Abstract: We discuss a case of a female runner who presented with burning left groin and thigh pain and positional swelling after a long run. The workup revealed May‐Thurner syndrome. May‐Thurner syndrome anatomy is a common anatomical variant present in approximately 20% of the population. Compression of the iliac vein may result in venous stasis in the lower limb with a predisposition to deep venous thrombosis. We identify 4 reported cases of May‐Thurner syndrome in female runners and review the importance of diagnosis and appropriate treatment of this condition. Level of Evidence: V